Faktor-faktor yang memengaruhi perilaku konsumtif masyarakat Indonesia dalam berbelanja online - Amalya, Meyfa Nur Alfu Laila (Maliki Interdisciplinary Journal, 2023)
Technology and the internet that are developing rapidly in Indonesia have changed the lifestyle and behavior of people to become consumptive because of online shopping. This study aims to determine the factors that motivate people to make purchases through online shops. This study uses a qualitative approach. Based on research results, technological advances really help people to reach all information as well as convenience when shopping online. Factors that influence consumptive behavior when shopping online are self-concept, lifestyle, and the reference group for consumptive behavior is divided into 3 namely; impulsive buying/purchasing impulse; non-rational buying/purchases are not rational; and wasteful buying/waste. And several aspects of consumptive behavior are divided into 3 namely; impulsive buying/purchasing impulse; non-rational buying/purchases are not rational; and wasteful buying/waste. The importance of public awareness in taking full advantage of the convenience of online shopping without being consumptive, also considering what is really necessary and useful when shopping online and prioritizing which products are really needed and must be purchased